"Dark" student volunteers: commitment, motivation, and leadership. Issue 5 (18th December 2019) - Veres, Jennifer Chelsea; Eva, Nathan; Cavanagh, Andrew
Abstract : Purpose: Drawing from the cognitive evaluation theory, the purpose of this paper is to explore the relationship between student volunteers' narcissism, Machiavellianism and psychopathy, and commitment to university volunteer programmes through the mediating mechanisms of self-orientation and pro-social motivation. Further, it investigates the roll of servant leadership in mitigating these personality types and encouraging student volunteers to become more pro-socially motivated. Design/methodology/approach: The study uses data collected via questionnaire from 156 student volunteers across Australia. Hypothesis testing was conducted using ordinary least squares regression with the path-analytic conditional process modelling (PROCESS) macro for SPSS. Findings: The study's analysis indicated that self-orientated motivation mediated the relationship between narcissism and normative commitment, and pro-social motivation mediated the relationship between both Machiavellianism and psychopathy, and affective commitment. Further, servant leadership was found to moderate the relationship between both Machiavellianism and psychopathy, and pro-social motivation, such that the negative relationship became weaker under a servant leader. These findings suggest that servant leaders play a significant role in encouraging "dark" personalities to see the light. Originality/value: This research is the first to examine the use of the Dark Triad in a student volunteering context. It extends the cognitive evaluation theory by revealing that extrinsic (in contrast to intrinsic) motivations are "crowded out" as intrinsic (in contrast to extrinsic) motivations develop within individuals. The study also refines the social learning theory, by examining the influences of "positive" leadership attributes (servant leadership) on "darker" (Dark Triad) personalities.